Microalgae growth and oxygen production on different textile fabrics - Ewin Tanzli; Bennet Brockhagen; Inken Blanka Post; Thorsten Bache; Khorolsuren Tuvshinbayar; Sarah Vanessa Homburg; Andrea Ehrmann (Communications in Development and Assembling of Textile Products, 2022)
Microalgae can be used for diverse applications in research and industry. Several microalgae grow adhering to surfaces that are usually two-dimensional. A third dimension could increase the amount of microalgae adhering to a given area and can be offered by textile fabrics. Here we report on the microalgae Chlorella vulgaris and Scenedesmus spec. growing on different knitted fabrics under defined light and under office light conditions. Our results show a significant influence of illumination on both algal species and a smaller impact of the chosen medium, while all knitted fabrics under examination were found well suited as substrates. The numbers of alga cells per petri dish were higher on textile fabrics than in pure water or medium by a factor of ~ 4–20, respectively.